Comparative Study of Generating Metacognitive Competence Strategy of Elementary School Students - Yuliana Setyaningsih; Fransisca Despa Listiani; Kristophorus Divinanto Adi Yudono (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
This study aims to compare teachers' strategy in generating students’ metacognitive abilities in elementary schools. The substantive data source of this research is the texts produced by transcription of teacher's speech records in carrying out the teaching-learning process with students in which there are strategies for generating students' metacognitive abilities. The locative data sources of this research are Demangan Baru Kanisius Elementary School Yogyakarta (Elementary School A) and Pius Bhakti Utama Elementary School Kutoarjo (Elementary School B). The data of this study were the form of speech footage from the transcription of teacher records containing strategies for generating students' metacognition. The data collection method used was the method of listening, both referring to both involved and able to see and be involved freely. The technique used was the note taking technique and record technique. Furthermore, the data analysis method used was the content analysis method. The results of the study were presented by the informal presentation method. The results indicated that the metacognitive competence generation strategies undertaken by teachers in School A and School B include the following strategies: (1) affirm critical thinkers' self-worth, (2) listen attentively to critical thinkers, (3) show that you support critical thinkers 'efforts, (4) reflect and mirror critical thinkers' ideas and actions, (5) motivate people to think critically, (6) regularly evaluate progress, (7) help critical thinkers create networks, (8) be critical teachers . The strategy of making people aware of how they learn critical thinking is only implemented in one school. The realization of students’ metacognitive competence strategies in the two schools varies according to the experience of the teacher in teaching, the background of students' abilities, and the perspective of the teachers in learning, etc.